Depiction of Shiva and Parvati on Nandi - Temples of India Project Team (Jio Institute, 2024)
There are sculptures inside deep niches just below the flat ceilings of the aisles of the mandapa (pillared hall). This sculpture is of Shiva and Parvati on Nandi, of which the Parvati’s sculpture is broken. The main sculpture is flanked by two attendants. There is a second niche that is beyond the attendants which has a gavaksha (dormer window) motif.